Rupatadine in Established Treatment Schemes Improves Chronic Spontaneous Urticaria Symptoms and Patients' Quality of Life: a Prospective, Non-interventional Trial. Issue 4 (December 2015) - Metz, Martin; Weller, Karsten; Neumeister, Claudia; Izquierdo, Iñaki; Bödeker, Rolf-Hasso; Schwantes, Ulrich; Maurer, Marcus
Abstract Introduction Chronic spontaneous urticaria (CSU) is a common and hard to treat condition associated with a substantial negative impact on patients' quality of life (QoL). Clinical studies have shown that rupatadine is effective and safe in the treatment of CSU, but data from routine clinical care are scarce. Therefore, we assessed the effectiveness and tolerability of rupatadine in established dosages on CSU activity and patients' QoL in a routine daily practice setting. Methods This was an open, prospective, non-interventional study performed in 146 dermatological practices in Germany. CSU patients for whom treatment with rupatadine was indicated were eligible to participate. Key symptoms of urticaria activity and their impact on patients' QoL were assessed at the beginning and the end of treatment. Adverse events (AEs) and withdrawals, as well as the dosage regimens chosen, were documented. Patients and physicians were requested to rate effectiveness and tolerability of therapy at the final visit. All statistical analyses were descriptive. Results The majority of the 660 patients screened to be treated (median age 44 years, IQR = 31–59 years, n = 654) received rupatadine 10 mg tablets once (477 patients) or twice (105 patients) daily for a median time of 28 days. After treatment, 93.2% of the patients (606/650) reported a clear overall improvement of symptoms. Rupatadine significantly reduced the urticaria activity score (UAS7) as well as the frequency and severity of existing angioedema episodes. Similarly all domains of the urticaria-specific QoL questionnaire (CU-Q2 oL) were markedly improved. The majority of physicians and patients rated rupatadine treatment as effective and well tolerated. There were 39 (5.9%) early treatment withdrawals, and 21 patients (3.2%) experienced AEs. Conclusion Rupatadine when given according to the routine treating schemes improves symptoms and CU-Q2 oL of CSU patients; the drug is also safe and well tolerated. Funding Dr. R. Pfleger GmbH.